Crystal structure of a calcium(II)–pyrroloquinoline quinone (PQQ) complex outside a protein environment. Issue 12 (5th November 2020) - Lumpe, Henning; Mayer, Peter; Daumann, Lena J.
Abstract : Pyrroloquinoline quinone (PQQ) is an important cofactor of calcium‐ and lanthanide‐dependent alcohol dehydrogenases. The crystal structure of a Ca–PQQ complex (Ca3 PQQ2 ·13H2 O) is reported for the first time outside a protein environment. Abstract : Pyrroloquinoline quinone (PQQ) is an important cofactor of calcium‐ and lanthanide‐dependent alcohol dehydrogenases, and has been known for over 30 years. Crystal structures of Ca–MDH enzymes (MDH is methanol dehydrogenase) have been known for some time; however, crystal structures of PQQ with biorelevant metal ions have been lacking in the literature for decades. We report here the first crystal structure analysis of a Ca–PQQ complex outside the protein environment, namely, poly[[undecaaquabis(μ‐4, 5‐dioxo‐4, 5‐dihydro‐1 H ‐pyrrolo[2, 3‐ f ]quinoline‐2, 7, 9‐tricarboxylato)tricalcium(II)] dihydrate], {[Ca3 (C14 H3 N2 O8 )2 (H2 O)11 ]·2H2 O} n . The complex crystallized as Ca3 PQQ2 ·13H2 O with Ca 2+ in three different positions and PQQ 3−, including an extensive hydrogen‐bond network. Similarities and differences to the recently reported structure with biorelevant europium (Eu2 PQQ2 ) are discussed.